Leadership: A Critical Text - Simon Western (SAGE Publications, 2008)
Providing a critical review and analysis of the key debates within leadership, this book challenges the notion of the individual or hero leader. The author develops the idea of leadership as a distributed process between lots of agents in an organization. In doing so he provides a new framework which readers can use to understand and implement this distributed type of leadership.